Duplication of the autism-related gene Chd8 leads to behavioral hyperactivity and neurodevelopmental defects in mice - Atsuki Kawamura; Kazuki Fujii; Kota Tamada; Yoshifumi Abe; Kenta Nitahara; Tomoya Iwasaki; Sho Yagishita; Kenji F. Tanaka; Toru Takumi; Keizo Takao; Masaaki Nishiyama (Nature Communications)
Abstract Mutations in the gene encoding chromodomain helicase DNA-binding protein 8 (CHD8) are strongly associated with autism spectrum disorder (ASD). Although duplications of the chromosomal locus including CHD8 have also been detected in individuals with neurodevelopmental disorders, the contribution of CHD8 duplication to clinical phenotypes and the underlying mechanisms have remained unknown. Here we show that Chd8 knock-in (KI) mice that overexpress CHD8 as a model of human CHD8 duplication manifest growth retardation, microcephaly, impaired neuronal differentiation, and behavioral abnormalities including hyperactivity and reduced anxiety-like behavior. Chd8 overexpression affects the transcription and chromatin accessibility of genes related to neurogenesis, with these changes being associated with aberrant binding of CHD8 to enhancer regions. Furthermore, pharmacological intervention partially ameliorates the hyperactivity of Chd8 KI mice. Our results thus indicate that Chd8 KI mice recapitulate key features of CHD8 duplication syndrome in humans, providing insight into pathogenic mechanisms underlying neurodevelopmental disorders.